2019
DOI: 10.1055/s-0039-1691785
|View full text |Cite
|
Sign up to set email alerts
|

Comparing Outcomes for Fasciocutaneous versus Muscle Flaps in Foot and Ankle Free Flap Reconstruction

Abstract: Background The distal lower extremity poses unique reconstructive challenges due to its requirements for durability of the load-bearing plantar surface and for thin, pliable contour in the dorsal foot and ankle region. This study compares outcomes between muscle and fasciocutaneous flaps in patients with foot and ankle defects. Methods A retrospective review of soft tissue free flaps used for traumatic foot and ankle defects was performed. Outcomes included takebacks, partial flap failure, total fl… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

1
46
0

Year Published

2019
2019
2023
2023

Publication Types

Select...
8
2

Relationship

0
10

Authors

Journals

citations
Cited by 42 publications
(47 citation statements)
references
References 42 publications
1
46
0
Order By: Relevance
“…The extensive experience of foot and ankle reconstruction using free tissue transfer by Lee et al is a valuable contribution to the field. 1 However, we have reservations about the conclusions, which are at odds with the data presented.…”
mentioning
confidence: 73%
“…The extensive experience of foot and ankle reconstruction using free tissue transfer by Lee et al is a valuable contribution to the field. 1 However, we have reservations about the conclusions, which are at odds with the data presented.…”
mentioning
confidence: 73%
“…Fasciocutaneous flaps, with its vast application opportunities have evolved into workhorse flaps for soft tissue reconstruction after trauma, showed lower recurrence rates after osteomyelitis and lower complication rates compared with muscle flaps for lower extremity reconstruction. 20,21 The study underlines the relevance of fasciocutaneous flap and is the reason why it is indicated as the workhorse flap for extremity reconstruction in our department. Approximately 54% of all free flaps of cohort A and 33% of cohort B were ALT flaps.…”
Section: Discussionmentioning
confidence: 95%
“…Similar to our results, the NYU group recently reported a lower rate of wound breakdown/ulcerations with fasciocutaneous (13.0%) versus muscle (28.6%) flaps on the weightbearing surface in the adult population, but again this was not statistically significant due to small sample size. 26 While our preference is for fasciocutaneous flaps, we acknowledge the literature on reconstruction of the weight-bearing surface is inconclusive. Two separate systematic reviews did not find differences in wound breakdown between muscle and fasciocutaneous flaps on weight-bearing surfaces.…”
Section: Discussionmentioning
confidence: 99%